1990
DOI: 10.1063/1.459408
|View full text |Cite
|
Sign up to set email alerts
|

Role of the long-range oscillatory tail of the effective pair potential in determining the structure of liquid metals

Abstract: To investigate the role of the long-range oscillatory part of the effective pair potential in determining structural features of liquid metals, the structure factor S(q) and the pair correlation function g(r) calculated for the full pair potential are compared with those obtained for various cutoff forms of the pair potential. The calculations are performed by employing the modified hypernetted-chain approximation, which is one of the best approximations in the integral equation theory of liquid. The results f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 16 publications
1
18
0
Order By: Relevance
“…In a series of investigations, it has been shown that the LJ(6-3) potential model, can be applied to predict the thermodynamic properties of liquid cesium metal quite accurately 26 . The form of the repulsion wall has been estimated by the application of neutron scattering data of liquid cesium metal 27,28 , and the attraction branch has been inspired by the form of dipole-dipole interaction potential 29,30 . In the same way, Exp-6 potential function has been shown to describe the properties of cesium liquid metal quite accurately 31 .…”
Section: Introductionmentioning
confidence: 99%
“…In a series of investigations, it has been shown that the LJ(6-3) potential model, can be applied to predict the thermodynamic properties of liquid cesium metal quite accurately 26 . The form of the repulsion wall has been estimated by the application of neutron scattering data of liquid cesium metal 27,28 , and the attraction branch has been inspired by the form of dipole-dipole interaction potential 29,30 . In the same way, Exp-6 potential function has been shown to describe the properties of cesium liquid metal quite accurately 31 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, due to the attraction part in the screened potential, at r s = 1.8 the peak in the RPDF of ions interacting through the STLS screened potential is much higher than that of the YOCP with pair potential (11). Such an effect is not visible at r s = 1.5 because the asymptote of the potential has a pattern of oscillations around zero with closely enough situated extrema so that the effect of the repulsive and attractive parts of the pair potential mutually compensated [96], similar to the case r s = 1 (see Fig. 8).…”
Section: B Density Rs = 2: Non-ideal Electronsmentioning
confidence: 94%
“…The results indicate that at high densities the pair correlation function is affected mainly by the short range repulsive part of the pair potential and that the long range attractive part only affects the height of the first peak [17]. The results, however, obtained for liquid Cs metal have been in sharp contrast with normal fluid [17]. Typically, at high density of liquid Cs (e.g.,…”
Section: Introductionmentioning
confidence: 90%
“…The method is quite accurate and sensitive to the detail of potential function. It has been used successfully to investigate the role of the tail of potential function on the pair correlation function near triple point of liquid cesium [17].…”
Section: Pair Correlation Function and Structure Factormentioning
confidence: 99%